COVID-19 vaccine confidence and its effect on vaccine uptake among people with hypertension or diabetes mellitus in Kilimanjaro region, Tanzania - Monica Mtei; Daimon Mwasamila B; Caroline Amour; Julieth S Bilakwate; Laura J Shirima; Amina Farah; Innocent B Mboya; James Ngocho; Johnston M George; Sia E Msuya (Human Vaccines & Immunotherapeutics, 2024)
COVID-19 vaccination effectively reduces disease severity, hospitalization, and mortality, particularly among individuals with chronic conditions who bear a disproportionate burden of disease complications. Vaccine confidence – belief in its safety, effectiveness, and importance – boosts uptake. However, limited data on vaccine confidence in this population hinders the development of targeted interventions. This study examined COVID-19 vaccine confidence and its impact on uptake among individuals with hypertension or diabetes mellitus in the Kilimanjaro region, Tanzania. A community-based cross-sectional study was conducted in March 2023 among 646 randomly selected adults aged ≥18 years with hypertension or diabetes mellitus in three districts of Kilimanjaro region, northern Tanzania. An interviewer-administered electronic questionnaire assessed confidence and uptake of COVID-19 vaccines in addition to related knowledge and demographic characteristics. Data analysis was done for 646 individuals who consented to participate. Multivariable logistic regression models determined the factors associated with COVID-19 vaccine confidence and its effect on vaccine uptake. The proportion of COVID-19 vaccine confidence among all 646 participants was 70% and was highest for perceived vaccine importance (80%), followed by perceived vaccine effectiveness (77%) and perceived vaccine safety (74%). Good knowledge of COVID-19 vaccines and living in the Mwanga municipal council (MC), a semi-urban district, was independently associated with confidence in the vaccines’ importance, safety, effectiveness, and overall COVID-19 vaccine confidence. Confidence in COVID-19 vaccines increased the odds of vaccine uptake. Targeted interventions to boost vaccine confidence are therefore essential to enhance vaccine uptake in this high-risk population.